Fleet operations at fishing of japanese sardine and chub mackerel in the Kuril waters in the modern period of high abundance of these species - O. N. Kruchinin; M. A. Mizyurkin; E. A. Zakharov; V. M. Volotov; D. L. Shabelsky; N. L. Vakker (Известия ТИНРО)
Chub mackerel and japanese sardine fishery is overviweved for the period since 1976. Two blooms of high abundance were observed within this period for both species. Effectiveness of fishing methods used during the past and the present blooms is compared to reveal prospects for their improvement and to sunstantiate the operating parameters of fishing gear suitable for energy capabilities of fishing vessels with certain tonnage. On results of this analysis, wider use of purse seine is recommended for landing of japanese sardine, as the more effective and resource-saving technology. The fish could be poured from the seine by either coupler or fish pump; the fish pump is recommended for trawl vessels, as well.